If f : R→R is given by


If $f: R \rightarrow R$ is given by $f(x)=x^{3}+3$, then $f^{-1}(x)$ is equal to

(a) $x^{1 / 3}-3$

(b) $x^{1 / 3}+3$

(c) $(x-3)^{1 / 3}$

(d) $x+3^{1 / 3}$



Let $f^{-1}(x)=y$


$\Rightarrow y^{3}+3=x$

$\Rightarrow y^{3}=x-3$

$\Rightarrow y=\sqrt[3]{x-3}$

$\Rightarrow y=(x-3)^{\frac{1}{3}}$

So, the answer is (c).

Leave a comment


Click here to get exam-ready with eSaral

For making your preparation journey smoother of JEE, NEET and Class 8 to 10, grab our app now.

Download Now